PAPR reduction using selected codeword shift (SCS) technique and SCS-SLM technique for space time coding MIMO-OFDM / Ezmin Abdullah - Abdullah, Ezmin (Institute of Graduate Studies, UiTM, 2017)
In the world of increasing mobility, the emerging needs for the cellular and wireless communications have increased enormously. The demand of efficient, reliable and also high speed wireless communications network can be achieved by implementing multiple input multiple output (MIMO) and orthogonal frequency division multiplexing (OFDM). However, in recent years, information technology has progressively led to global energy consumption due to the demands of mobile communications around the world. In this level, the main component to reduce power consumption depends on the high-power amplifier (HPA) efficiency which is associated to the peak-to-average power ratio (PAPR). However, various techniques that have been proposed to reduce the high PAPR are encountered with some drawbacks such as computational complexity and bit error rate (BER) degradation. These drawbacks are due to the formulation and algorithm of the PAPR reduction techniques in the OFDM system to achieve substantial PAPR reduction. In this thesis, a new formulation for interleaving technique using circulant shift is proposed to form an optimum permutation for interleaving technique. In addition, an appended bit side information (SI) is proposed to avoid the BER degradation at the receiver…